Expert Answers
justaguide eNotes educator| Certified Educator

The equation 3*ln(x-3) + 4 = 5 has to be solved

3*ln(x-3) + 4 = 5

=> 3*ln(x-3) = 1

=> ln(x - 3) = 1/3

=> (x - 3) = e^(1/3)

=> x = e^(1/3) + 3

The required solution of the equation is x = e^(1/3) + 3

thilina-g eNotes educator| Certified Educator

3*ln(x-3)+4 = 5

3*ln(x-3) = 5 -4 = 1

ln(x-3) = 1/3

x -3 = e^(1/3)

x = e^(1/3) + 3 = 1.3956 + 3

x = 4.3956

Access hundreds of thousands of answers with a free trial.

Start Free Trial
Ask a Question